Wanprestasi dan PKPU: Kewajiban Sentul City dalam Sengketa Kepailitan - Syahla Pridehan; Velissa Maharani; Akmal Zaki; Dwi Desi Yayi Tarina (Lembaga Pengembangan Kinerja Dosen, 2025)
The case of Postponement of Debt Payment Obligations (PKPU) of PT Sentul City Tbk is one example of the complexity of dispute resolution between corporations and creditors. The PKPU application was filed by PT Prakasaguna Ciptapratama on January 7, 2021 at the Central Jakarta Commercial Court on the grounds that there was a debt due that had not been paid. Although the peace plan had been approved by the majority of creditors and ratified by the court on March 15, 2021, some consumers who felt aggrieved filed for a Judicial .Review (PK). They based their lawsuit on the postponement of the signing of the Deed of Sale and Purchase (AJB) which had lasted for more than 15 years. This study aims to analyze the legal aspects, financial implications, and social impacts of this case, including an evaluation of the PKPU mechanism in resolving debt disputes in Indonesia.